Analysis of Demand and Competition for Indonesian Frozen Tilapia Fillet with Major Competitors in the International Market - Mutiara Ria Despita Maharani; Muhammad Ali Yafi; Musyafak Musyafak (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
Frozen tilapia fillets are the only farmed fish among Indonesia's leading fishery export commodities. Fierce competition requires Indonesia to maintain its position. This study aims to analyze the demand for and competition with major competitor countries in the international market for Indonesian frozen tilapia fillets. This study employs the Almost Ideal Demand System (AIDS) and estimates it using the Seemingly Unrelated Regression (SUR) method. The data source is secondary data obtained from ITC Trade Map with HS code 030461 (Frozen fillets of tilapia "Oreochromis spp."). The analysis is based on panel data with monthly time series from 2014 to 2024. Meanwhile, cross-sectional data uses China, Taiwan, the Netherlands, and the USA as Indonesia's main competitors. The findings indicate that demand for Indonesian frozen tilapia fillets is price-inelastic, meaning it is relatively unresponsive to price changes. Indonesian frozen tilapia fillets are classified as inferior goods with an elasticity value of -0.478. This implies that a rise in consumer income will actually reduce demand. The cross-price elasticity indicates that Indonesia tends to compete with China, Taiwan, the Netherlands, and the USA. This is because the relationship between Indonesian frozen tilapia fillet and competing countries is one of substitution. The findings of this study reveal that Indonesia must focus on strategies to improve product quality and production efficiency in order to strengthen its position in the global market. Exporters need to increase the value of their products through diversification, quality certification, and compliance with international standards in order to survive and compete with rival countries.